2017
DOI: 10.1093/hmg/ddx328
|View full text |Cite
|
Sign up to set email alerts
|

Exome-wide association study reveals novel psoriasis susceptibility locus at TNFSF15 and rare protective alleles in genes contributing to type I IFN signalling

Abstract: Psoriasis is a common inflammatory skin disorder for which multiple genetic susceptibility loci have been identified, but few resolved to specific functional variants. In this study, we sought to identify common and rare psoriasis-associated gene-centric variation. Using exome arrays we genotyped four independent cohorts, totalling 11 861 psoriasis cases and 28 610 controls, aggregating the dataset through statistical meta-analysis. Single variant analysis detected a previously unreported risk locus at TNFSF15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…In addition to informing the targets of biologic medications, genetic studies have opened new avenues for small molecule therapeutics. Following genetic association data highlighting TYK2 as a causal allele (31,32), an oral, selective Theme issue: Psoriasis inhibitor was developed, which has shown promising efficacy in phase II trials (57).…”
Section: Translation Of Genetic Discoveries Into Novel Therapeuticsmentioning
confidence: 99%
“…In addition to informing the targets of biologic medications, genetic studies have opened new avenues for small molecule therapeutics. Following genetic association data highlighting TYK2 as a causal allele (31,32), an oral, selective Theme issue: Psoriasis inhibitor was developed, which has shown promising efficacy in phase II trials (57).…”
Section: Translation Of Genetic Discoveries Into Novel Therapeuticsmentioning
confidence: 99%
“…In subsequent studies, haplotype analysis showed that the rs2304256 association in SLE and RA is likely driven by imperfect LD to the independent causal variants rs34536443 (P1104A), rs12720356 (I684S) or rs35018800 (A928V) [50]. A similar conclusion was reached in a study of systemic sclerosis patients and in a meta-analysis using exome arrays to identify psoriasis-associated rare variants [51,52]. Recently, a fine mapping analysis of causal variants for RA and IBD identified rs34536443 and rs12720356, but not rs2304256 [53].…”
Section: Discussionmentioning
confidence: 62%
“…Genetic studies support its implication in autoimmune diseases and mycobacterial infections. Case-control and GWA studies have identified Tnfsf15 gene variants, such as rs6478108 alleles, that associate with increased susceptibility to psoriasis and psoriatic arthritis in populations of European descent (111, 112). Furthermore, alleles rs6478108 (T) and rs4979462 (T), have been found to increase susceptibility to both Primary Billiary Cholangitis (PBC) and CD, while protecting from leprosy (6, 113).…”
Section: Tl1a/dr3 In the Crossroads Of Systemic Inflammation: Associamentioning
confidence: 99%